Mechanisms of formation of targeted insertions under the synthesis of a DNA molecule containing cis-syn cyclobutane cytosine dimers - Grebneva, H.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
A polymerase – tautomer model of ultraviolet mutagenesis is developed. The mechanism of formation of targeted insertions that is caused by cis-syn cyclobutane cytosine dimers is proposed. Insertions are frameshift mutations, when one or several DNA bases are inserted. Structural analysis has shown that, opposite two rare tautomeric forms of cytosine, it is impossible to insert any canonical DNA bases with template bases with the formation of hydrogen bonds. Therefore, under the synthesis of DNA containing cis-syn cyclobutane cytosine dimers with cytosine molecules in such rare tautomeric forms, specialized or modified DNA polymerases will leave one nucleotide gaps opposite these cis-syn cyclobutane cytosine dimers. On DNA sites with homogeneous nucleotide composition, the end of a DNA strand may slip and join with hydrogen bonds so that a loop is formed by the Streisinger model. As a result, the daughter strand is elongated, and the targeted insertion is formed.